Pelatihan Pembuatan Sabun Cuci Piring Berbasis Eco-Enzyme Sebagai Upaya Menumbuhkan Jiwa Wirausaha Siswa SMA Muhammadiyah 3 Jember - Afan Bagus Mananda; Ara Nugrahayu Nalawati; Retno Murwanti; Danu Indra Wardhana; Andika Putra Setiawan; Alda Wata Alim; Nanda Putri Eryani (Journal of Community Development, 2024)
One of the big problems facing Indonesia is unemployment and waste management. The Central Statistics Agency (BPS) recorded February 2023 data that there were still 7.99 million unemployed in Indonesia. In terms of education, the highest unemployment rate (TPT) is experienced by high school (SMA) and vocational high school (SMK) graduates. One of the efforts to reduce the high number of unemployed, Senior High Schools (SMA) are expected to play an active role in producing graduates who can create jobs. The waste problem in Indonesia is also a problem that has not been resolved to date. Indonesia is estimated to produce 187.2 million tons of waste every year, with 60% coming from organic waste. One solution for handling organic waste is the application of Eco-enzyme. The aim of this activity is to provide training in making Eco-Enzyme based dish washing soap as an effort to foster the entrepreneurial spirit of students at SMA Muhammadiyah 3 Jember. This activity was carried out in the form of direct outreach and training to 75 students. Based on the results of observations of these activities, SMA Muhammadiyah 3 Jember has never implemented making dishwashing soap from organic waste. This can be seen from the pre-test with the results that only 21% of students had a good level of knowledge about Eco-Enzyme. Furthermore, the post-test results after carrying out this training, those with good knowledge levels increased to 92%. The pretest and posttest results show that on average the training participants experienced an increase in knowledge and understanding about the Eco-Enzyme-based Dish Soap Making Training, so it is hoped that it can motivate students' entrepreneurial interest by thinking creatively and innovatively.